Environmental Impact Assessment of Recycled Wastes on Surface and Ground Waters Engineering Modeling and Sustainability - Kassim, Tarek A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The state of the art of the impact assessment of recycled hazardous waste materials on surface and ground waters is presented. The topics include chemodynamics, toxicology, modeling and information systems. Due to the wealth of information on this topic, the texts of T. Kassim (ed.): Environmental Impact Assessment of Recycled Wastes on Surface and Ground Waters are published in three separate volumes: vol. 1: Concepts, Methodology and Chemical Analysis; vol. 2: Risk Analysis and vol. 3: Engineering Modeling and Sustainability. The book serves as a practical conceptual guide for those who have professional responsibility for the monitoring, design, management, or conduct of environmental impact assessment. It is believed that the book will prove useful to the reader who, regardless of disciplinary background, wants to examine in greater detail the kinds of interdisciplinary contributions to contemporary decision-making processes that characterize modern impact assessment project development. Each volume contains the contents of all volumes.
Keywords: Water pollution; Water quality; Environmental pollution; Environmental management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Terrestrial Pollution; Environmental Management